2021
DOI: 10.1159/000519491
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review: Reappraisal of Uric Acid in Chronic Kidney Disease

Abstract: Hyperuricemia predicts the development of chronic kidney disease (CKD) and metabolic complications, but whether it has a causal role has been controversial. This is especially true given the 2 recently conducted randomized controlled trials that failed to show a benefit of lowering uric acid in type 1 diabetes-associated CKD and subjects with stage 3–4 CKD. While these studies suggest that use of urate-lowering drugs in unselected patients is unlikely to slow the progression of CKD, there are subsets of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 89 publications
0
10
0
2
Order By: Relevance
“…Uric acid has been associated with CV diseases and with inflammation and oxidative stress. In addition, the majority of these studies showed that elevated levels of uric acid are a potential contributor risk factor in the development and progression of CKD [ 186 , 187 ].…”
Section: Improvement Of Conventional CV and Renal Risk Factors By Sgl...mentioning
confidence: 99%
“…Uric acid has been associated with CV diseases and with inflammation and oxidative stress. In addition, the majority of these studies showed that elevated levels of uric acid are a potential contributor risk factor in the development and progression of CKD [ 186 , 187 ].…”
Section: Improvement Of Conventional CV and Renal Risk Factors By Sgl...mentioning
confidence: 99%
“… 75 Finally, elevated uric acid levels have been associated with increased renal inflammation and oxidative stress and, in this context, SGLT2i would promote an increased glycosuria-associated uricosuric action. 76 …”
Section: Reviewmentioning
confidence: 99%
“…11 Although recent studies are mixed as to whether urate lowering is actually renally protective, evidence suggests that some patient subsets, including those with gout, may be more likely to benefit. 33 Overall, when choosing among multiple antihypertensive agents, the selection of losartan, particularly over other agents that can raise sU levels, can significantly affect a patient's sU level and may have additional benefits. For this reason, the 2020 ACR gout treatment guideline conditionally recommends "choosing losartan preferentially as an antihypertensive agent for patients with gout."…”
Section: Antihypertensivesmentioning
confidence: 99%